A Systematic Framework for Optimizing a Sweeping Gas Membrane Distillation (SGMD) - Nawras N. Safi; Salah. S. Ibrahim; Nasser Zouli; Hasan Shaker Majdi; Qusay F. Alsalhy; Enrico Drioli; Alberto Figoli (Membranes, 2020)
The present work has undertaken a meticulous glance on optimizing the performance of an SGMD configuration utilized a porous poly (vinylidene fluoride-co-hexafluoropropylene) (PVDF-co-HFP) membrane. This was carried out by conducting a systematic framework for investigating and optimizing the pertinent parameters such as sweeping gas flow rate, feed temperature, feed concentration and feed flow rate on the permeate flux. For this purpose, the Taguchi method and design of experiment techniques were harnessed to statistically determine optimum operational conditions. Besides that, a comprehensive surface and permeation characterization was conducted against the hand-made membranes. Results showcased that the membrane performance was ultimately controlled by the feed temperature and was nearly (~680) % higher when the temperature raised from 45 to 65 °C. Also, to a lesser extent, the system was dominated by the feed flow rate. As the adopted feed flow rate increases (from 0.2 to 0.6 L/min), around 47.5% increment was bestowed on water permeability characteristics. In contra, 34.5% flux decline was witnessed when higher saline feed concentration (100 g/L) was utilized. In the meantime, with raising the sweeping gas flow rate (from 120 to 300 L/h), the distillate was nearly 129% higher. Based on Taguchi design, the maximum permeate flux (17.3 and 17 kg/m2·h) was secured at 35 g/L, 0.4 L/min, 65 °C and 300 L/h, for both commercial and prepared membranes, respectively.